2019
DOI: 10.3390/atmos10110720
|View full text |Cite
|
Sign up to set email alerts
|

Recently Strengthened Influence of ENSO on the Wintertime East Asian Surface Air Temperature

Abstract: Previous studies have indicated that El Niño–Southern Oscillation (ENSO) exerts a significant influence on the East Asian winter climate. This study reveals an interdecadal strengthening of the connection between ENSO and the East Asian surface air temperature (EAT) connection around the late 1990s and investigates the reason for this change. Before the late 1990s, the influence of ENSO on the EAT was weak, and the ENSO-related southerly wind anomalies were confined to the south of 30° N of East Asia. After th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…During the 2015/16 winter, average precipitation levels in south China (Guangdong, Guangxi and Hainan Provinces) reached historic values, exceeding those in perennial years by more than 1.6 times [53]. At the same time, the El Niño phenomenon also had a large impact on the variability of the atmosphere [54][55][56]. Thus, a series of related issues resulting from policy regulation and the El Niño phenomenon moved the median center of atmospheric XCO 2 concentrations to the east of China.…”
Section: Interannual Variations In Xcomentioning
confidence: 99%
“…During the 2015/16 winter, average precipitation levels in south China (Guangdong, Guangxi and Hainan Provinces) reached historic values, exceeding those in perennial years by more than 1.6 times [53]. At the same time, the El Niño phenomenon also had a large impact on the variability of the atmosphere [54][55][56]. Thus, a series of related issues resulting from policy regulation and the El Niño phenomenon moved the median center of atmospheric XCO 2 concentrations to the east of China.…”
Section: Interannual Variations In Xcomentioning
confidence: 99%
“…Zhang & Delworth, 2016), and this behavior may have the possibility to weaken the AL variability. Hence, both the effects of the internal climate variability, such as the PDO, and global warming on the weakened AL variability should be considered in future work (e.g., H. Gong et al, 2019;Roy, 2018). In addition, the magnitude of the SH variability in the observation also shows decadal variations, and it has a strengthening trend after the late-1990s (Figure 6a).…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated that the underlying SST variability over the North Pacific related to the Pacific Decadal Oscillation (PDO) can affect the decade changes of the AL, with the warm (cold) phase of the PDO corresponding to a strong (weak) AL magnitude (e.g., S. Chen et al, 2021;H. Gong et al, 2019;Oh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been pointed out that the Kuroshio anticyclonic anomalies can significantly modulate the influences of ENSO on the western Pacific winter climate (Gong et al, 2019). The existence of the Kuroshio anticyclone may decrease the pressure gradient between East Asia and the North Pacific, which facilitates the northward extension of the southerly wind anomalies from the anticyclone over the Philippines.…”
Section: Conclusion and Discussionmentioning
confidence: 99%